Analysis of Public Satisfaction with the Quality of Birth Certificate Making Services at The Public Service Mall (MPP) of Pandeglang Regency in 2025 - Nurdin, Ali; Resti, Resti (MID Publisher International, 2024)
This study aims to analyze public satisfaction with the quality of birth certificate issuance services at the Public Service Mall (MPP) of Pandeglang Regency in 2025. The increasing number of applications for new and renewed birth certificates, along with public complaints about slow service, serves as the main background of this research. Technical problems, such as system failures, often cause delays in administrative processes, affecting citizens’ perceptions of service quality. The study employs a quantitative method by distributing questionnaires to service recipients. The service quality assessment is based on nine indicators derived from the Indonesian Ministry of Administrative Reform Regulation (Permenpan RB) No. 14 of 2017 concerning Guidelines for Public Satisfaction Surveys. The findings reveal that the overall satisfaction score reached 80.37, categorizing the service quality as “Good.” However, the “Requirements” indicator received the lowest score (8.33) due to insufficient dissemination of information through physical notice boards, leading to public confusion regarding procedures. The research recommends that the service institution improve information delivery not only through social media but also via on-site information boards. Additionally, regular evaluation and system maintenance are needed to enhance digital service mechanisms and minimize technical disruptions that hinder public service performance.